Populasi dan Jenis Mikroba Kontaminan pada Biji Kakao Kering Fermentasi dari Jembrana, Bali - Aprilliani, Dewa Ayu Komang Tri; Suprapta, Dewa Ngurah; Sudarma, I Made (Agrotrop : Journal on Agriculture Science; Vol 14 No 3 (2024)DO - 10.24843/AJoAS.2024.v14.i03.p13, 2024)
Population a nd Types o f Microbial Contaminants i n Dry Fermented Cocoa Beans f rom Jembrana, Bali . Jembrana, Bali is a district that produces cocoa beans, but there was a decline in production in 2020-2021. One of the causes is microbial contamination that can reduce the quality of the beans. The aim of this study was to determine the population and types of contaminant microbes and the types of microbes that dominate dry fermented cocoa beans. The methode in this research were isolation of mikrobes contaminations in dry fermented cocoa beans by dilution metode and identification of the type of microbes contaminant using macroscopis and microscopis observation. Sampling was taken randomly in 6 different villages namely Pulukan, Nusa Sari, Poh Santen, Tegal Cangkring, Penyaringan and Yehembang villages. Identification was done by observing macroscopic and microscopic characteristics. Population data were analyzed using one way ANOVA. The highest population number was found in sample 2 of Nusa Sari Village with colonies 270 x 10 4 CFU/g. The lowest population was found in sample 4 taken from Tegal Cangkring Village with a population of 5 x 10 4 CFU/g of fermented dry cocoa beans. Types and numbers of microbes that dominate samples are Saccharomyces sp. 173,3 x 10 4 CFU/g, Aspergillus sp. 156,6 x 10 4 CFU/g, Rhizopus sp. 90 x 10 4 CFU/g, Penicilium sp. 15 x 10 4 CFU/g, Mucor sp. 10 x 10 4 CFU/g and Chrysosporium sp. 5 x 10 4 CFU/g. Based on the maximum limit of the Indonesian National Standard (SNI) number SNI 7388:2009, six samples from Jembrana Bali have not passed SNI.